2000
DOI: 10.1161/01.atv.20.4.940
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Mitogen-Activated Protein Kinases in Smooth Muscle Cells by Angiotensin II

Abstract: Abstract-The atherogenic effect of the renin-angiotensin system can be explained, in part, by the influence of its effector, angiotensin II (Ang II), on vascular smooth muscle cell (VSMC) growth. There is evidence that reactive oxygen species (ROS) play a role in the atherogenesis and activation of mitogen-activating protein (MAP) kinases, which are involved in proliferation and differentiation. The study was performed to further characterize the role of ROS in Ang II-mediated MAP kinase activation and the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 37 publications
8
140
0
3
Order By: Relevance
“…pendent (46) transduction pathways in SMCs. We showed that the NAD(P)H-mediated AP-1 activation is independent of ERK1/2 activation, as described previously in angiotensin IIand endothelin-stimulated SMCs in which NAD(P)H oxidase activates mitogen-activated protein kinase, p38, and/or JNK (46,47). Altogether, this work characterizes two new regulatory elements on the OPN promoter and suggests that UTP activates two parallel pathways in a coordinated manner in SMCs (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…pendent (46) transduction pathways in SMCs. We showed that the NAD(P)H-mediated AP-1 activation is independent of ERK1/2 activation, as described previously in angiotensin IIand endothelin-stimulated SMCs in which NAD(P)H oxidase activates mitogen-activated protein kinase, p38, and/or JNK (46,47). Altogether, this work characterizes two new regulatory elements on the OPN promoter and suggests that UTP activates two parallel pathways in a coordinated manner in SMCs (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, H 2 O 2 has been demonstrated to stimulate the activity of other transporters, namely NHE and Na/K/2Cl. NHE from Wistar [25] and SpragueDawley rat ventricular myocytes [26] were stimulated after exposure of cells to [38,39]. We previously showed that the increased intracellular H 2 O 2 in SHR PTE cells was attenuated when cells were cultured in medium supplemented with apocynin (a NADPH oxidase inhibitor) while in WKY PTE cells no effect was observed [20].…”
Section: Discussionmentioning
confidence: 99%
“…DPI, NAC, p22 phox siRNA, or catalase may inhibit the activation of p38 MAPK and JNK/SAPKmediated Rac1-dependent H 2 O 2 production. 32,33 The production of ROS and the activation of the p38 MAPK signaling pathways induce the expression of several redox-sensitive genes associated with atherogenesis. The direct interaction of TLR4 with NADPH oxidase is involved in LPS-mediated ROS generation and NF-B activation.…”
Section: Discussionmentioning
confidence: 99%